Social, Educational, Cultural Meanings of Children’s Summer Leisure: Theoretical Aspect (Laisvalaikio tyrimai, 2018)
Research background. Children’s summer leisure as non-formal cultural education (learning) environment in Europe and the United States is equally important as learning in a formal, institutionalized (school) environment. In these countries there is interest in children’s weekend, festive, school (including summer) vacation, leisure time. Lithuania is the opposite – a formal interest in school, leisure, entertainment and children’s informal cultural environment (after all, one of these environments is summer leisure environment) has not been almost studied. Children’s summer vacation became important because of its long duration – two / three months. Most parents and children’s summer vacation periods do not coincide, so adults worry about their children activity during the summer holidays. Then children’s summer leisure is overlooked, perceived as an adult controlled and proposed activity. The aim of the study is to justify social, educational, cultural meanings of children’s summer leisure. The object of the study is children’s summer leisure significance. Methods: theoretical analysis, meta-analysis. Results. The processes of democracy and liberalization occurring in modern society and the declared philosophy of humanism permit to investigate children’s leisure culture in summer as a social and educational phenomenon within the contexts of ‘free’ (self-) education and the phenomenon of freedom. Children’s leisure culture in summer is contextualized as the time disposed by children themselves and implicates social and educational meanings. In terms of such conceptions the child becomes an active creator of his/her leisure culture. The social and educational significance of children’s leisure culture in summer is perceived through the meanings attached by children themselves. Such interpretational paradigm of children’s leisure culture in summer turns out to be significant in creating new knowledge for educators (parents, teachers, specialists of non-formal education, etc.). Children’s narrative on summer leisure enables this discourse to be accepted in the science of education/pedagogy as overt/main rather than hidden/secondary one, existing alongside with the discourse created by adults ‘children are immature sociocultural individuals, therefore, unable to carry out an activity, which is significant for their (self-)education and (self)socialization’.Keywords: children’s summer leisure, non-formal education (learning) environment.